α-Galactosidase A Augmentation by Non-Viral Gene Therapy: Evaluation in Fabry Disease Mice - Julen Rodríguez-Castejón; Ana Alarcia-Lacalle; Itziar Gómez-Aguado; Mónica Vicente-Pascual; María Ángeles Solinís Aspiazu; Ana del Pozo-Rodríguez; Alicia Rodríguez-Gascón (MDPI AG, 2021)
Fabry disease (FD) is a monogenic X-linked lysosomal storage disorder caused by a deficiency in the lysosomal enzyme α-Galactosidase A (α-Gal A). It is a good candidate to be treated with gene therapy, in which moderately low levels of enzyme activity should be sufficient for clinical efficacy. In the present work we have evaluated the efficacy of a non-viral vector based on solid lipid nanoparticles (SLN) to increase α-Gal A activity in an FD mouse model after intravenous administration. The SLN-based vector incremented α-Gal A activity to about 10%, 15%, 20% and 14% of the levels of the wild-type in liver, spleen, heart and kidney, respectively. In addition, the SLN-based vector significantly increased α-Gal A activity with respect to the naked pDNA used as a control in plasma, heart and kidney. The administration of a dose per week for three weeks was more effective than a single-dose administration. Administration of the SLN-based vector did not increase liver transaminases, indicative of a lack of toxicity. Additional studies are necessary to optimize the efficacy of the system; however, these results reinforce the potential of lipid-based nanocarriers to treat FD by gene therapy.